Pengaruh Illnes Perception, Dukungan Sosial, dan Health Locus of Control terhadap Kepatuhan Pada Pasien Gagal Ginjal Kronik - Devi Wulandari (Universitas Paramadina, 2015)
Number of patient with kidney disease is increasing every year. Kidney disease as a chronic disease bring changes in the lives of patient .One of the implications of the changes that must be made is fluid restriction. Compliance with this fluid restriction is a problem for people with the kidney disease.There are various factors affecting patient compliance with chronic renal failure both internal and external.Factors that influence are seven aspects of illness perception (timeline acute chronic, timeline cyclical, personal control , treatment control, illness coherence, emotional representation, consequences) and three aspects of health locus of control (chance, powerful others, internal). External factor was the social support. This research aims to see the effect of the timeline acute chronic, timeline cyclical, personal control, treatment control, illness coherence, emotional representation, chance locus of control, powerful others, internal locus ofcontrol and social support for treatment adherence of patients with chronic renal failure. The study used a questionnaire distributed to 98 patients who were diagnosed with chronic kidney disease. This data analyzed using multiple regression analysis. The results showed protective factors that play a role in patient compliance with chronic renal failure are: powerful others and treatment control.The risk factors that play a role in patient compliance with chronic renal failure are: female, social support, timeline cyclical and emotional representation. Jurnal Universitas Paramadina Vol. 12 No. 1 Desember 2015 1254Keywords: Compliance, chronic renal failure, illness perception, health locus of control, social support